Supply chain integration, advanced manufacturing technology, and strategic leadership: An empirical study. (April 2019) - Birasnav, M.; Bienstock, Joshua
Highlights: Transactional leaders concentrate on internal integration. Transformational leaders concentrate on external integration. Advanced manufacturing technology is focused on external integration. Manufacturing technology moderates leadership and customer integration linkage. Abstract: Top management support is a crucial investment at any manufacturing firm striving to integrate supply chain partners with the manufacturing processes so as to achieve a competitive advantage. Though the effectiveness of different leadership behaviors exhibited in top-level management has been documented in the leadership literature, the influence of such behaviors on developing linkages with supply chain partners has not been extensively examined. In order to bridge this research gap, this study examines the interlinkages between strategic leadership theory and supply chain integration theory. In addition, it also investigates the interrelationships between these two theories in the context of implementation of advanced manufacturing technology. Data has been collected from 107 small manufacturing companies and was analyzed using structural equation modelling. Results show that transactional leadership exhibited in top-level management is positively related to internal integration within the manufacturing companies. Transformational leadership behavior exhibited in top-level management and advanced manufacturing technology implemented in the shop floor of these companies are positively related to the integration of external supply chain partners. In addition, we also found that in those instances where small manufacturing companies place a high emphasis on the implementation of advanced manufacturing technology, they are guided by transformational leaders who strongly integrate their companies with customers.